Novel equations for estimating gross energy in feed ingredients for non-ruminants - Yoon Soo Song; Ah Reum Son; Beob Gyun Kim (Animal Bioscience)
Objective The present study aimed to evaluate the accuracy of previous equations for estimating gross energy (GE) in feed ingredients and to develop the novel equations. Methods A total of 2,279 ingredient samples consisted of barley (n = 58), corn (n = 319), corn distillers dried grains with solubles (n = 13), corn gluten feed (n = 583), copra expellers (n = 156), copra meal (n = 234), cottonseed meal (n = 12), palm kernel expellers (n = 504), rapeseed meal (n = 114), soybean meal (n = 138), wheat (n = 70), and wheat bran (n = 78) were analyzed for dry matter (DM), crude protein (CP), ether extract (EE), crude fiber, ash, and GE. The 2,279 ingredient samples were used for evaluating the previous equations and developing novel equations. Using data from 62 ingredients in the swine NRC publication in 2012, the old equations and the novel equations were evaluated. Results Based on the evaluation using 2,279 samples, the equation developed by Ewan in 1989 underestimates GE by 218 kcal/kg DM (standard error = 4 and p<0.001) on average and underestimates more for low-GE ingredients (linear bias = −0.121; standard error = 0.025 and p<0.001). The equation reported by Sauvant, Perez, and Tran in 2004 also underestimates GE by 135 kcal/kg DM (standard error = 4 and p<0.001) on average. Novel equations for estimating GE concentration (kcal/kg DM) in feeds were developed: GE = 4,299+7×CP +53×EE, with R2 = 0.342 and p<0.001; GE = 4,341+11×CP+54×EE–24×ash, with R2 = 0.372 and p<0.001, where all independent variables are in % DM. In the validation using 62 feed ingredients in the NRC publication, the equations developed in the present study were accurate whereas the previous equations were not. Conclusion The novel equations developed in the present study fairly accurately estimate gross energy concentrations in concentrate feeds.